(untitled) (Journal of Engineering, 2024)
Several techniques are used to improve the channels’ heat transfer coefficient and Nusselt number. One of the methods used for these improvements is porous media (PM). This research deals with an experimental study of heat transfer by forced convection inside a square-shaped channel (0.12 x 0.12 m2) with a length of (0.5 m) and a hydraulic diameter of (0.12 m). The heat flux (4791.7 W/m2) is exposed below the test section, and other walls are thermally insulated. The air was used as the working fluid for the Reynolds number range (2689.6 to 5806.3). The channel was partially filled with the PM (glass spheres with 5mm diameter) by taking three different heights layers (20, 40, and 60 mm) and knowing its effect on the temperature distribution, the local heat transfer coefficient, locally Nusselt number, and the average heat transfer coefficient and Nusselt number. Also, the same parameters were studied without PM inside the channel (plain). The results showed that the PM improved the heat transfer coefficient and the Nusselt number. Also, the temperature distribution decreased gradually with the Reynolds number increase for each height layer, the local heat transfer coefficient and local Nusselt number gradually reduced with the length of the test section increase for each Reynolds number, average Nusselt number increased gradually with the growth of the Reynolds number for each height layer. The PM layer at a height of (60 mm) gave the best improvement in the heat transfer coefficient and Nusselt number compared to the other layers. In addition, the friction factor across the test section at this layer decreases gradually with increasing fluid velocity.